Monitoring virulence of Bremia lactucae as a breeding tool against lettuce downy mildew from south and southwest Brazilian regions - Franco, C. A. [UNESP] (2021)
Lettuce downy mildew caused by Bremia lactucae is one of the main diseases in high humidity and low temperature conditions. The identification of virulence factors appearing in the pathogen population could help improve breeding programs against this disease. This study aimed to monitor and evaluate virulence dynamic changes in B. lactucae virulence among two Brazilian regions to recommend resistance genes for breeding programs. Isolates from São Paulo, Rio Grande do Sul, and Paraná states were assessed using the sextet code EU-C composed by 16 Lactuca spp. genotypes, between 2015 and 2016. To understand the population dynamics, the frequencies of virulence phenotypes and factors and the virulence complexity per isolate (Ci), phenotype (Cp), and Gleason (Ig), indexes were calculated. B. lactucae virulence from Paraná, Rio Grande do Sul and São Paulo were similar and shared nine out of the 15 evaluated virulence factors. In total, 90 isolates were analyzed, and 27 virulence phenotypes were found. The most frequent sextet codes were 31–00-00, 31–00-02, 31–01-00, and 31–01-02. The genes or resistance factors present in ‘Argelès’ (Dm38), ‘Balesta’, and ‘Bartoli’ could be used as sources of resistance by Brazilian lettuce breeders.